Mapping macaque to human cortex with natural scene responses - Kasper Vinken; Saloni Sharma; Margaret S. Livingstone (Proceedings of the National Academy of Sciences, 2025)
Neuroscience has long relied on macaque studies to infer human brain function, yet identifying functionally corresponding brain regions across species and measurement modalities remains a fundamental challenge. This is especially true for the higher-order cortex, where functional interpretations are constrained by narrow hypotheses and anatomical landmarks are often nonhomologous. We present a data-driven approach for mapping functional correspondence across species using rich, naturalistic stimuli. By directly comparing macaque electrophysiology with human fMRI responses to 700 natural scenes, we identify fine-grained alignment based on response pattern similarity, without relying on predefined tuning concepts or hand-picked stimuli. As a test case, we examine the ventral face patch system, a well-studied but contested domain in cross-species alignment. Our approach resolves a long-standing ambiguity by supporting a correspondence between macaque ML and human FFA and between AL and more anterior temporal cortex in humans. This result is consistent with full-brain anatomical warping but inconsistent with prior studies limited by narrow functional hypotheses. These findings show that natural image-evoked response patterns provide a robust foundation for cross-species functional alignment, supporting scalable comparisons as large-scale primate recordings become more widespread.